Pain caused by measles, mumps, and rubella vaccines: A systematic literature review. Issue 42 (9th October 2017) - Willame, Corinne; Henry, Ouzama; Lin, Lan; Vetter, Volker; Baril, Laurence; Praet, Nicolas
Highlights: Injection site pain associated with vaccination can lead to vaccination hesitancy. We review evidence on injection site pain following MMR vaccination in children. Immediate (acute) pain: defined as pain occurring within 0–5 min of injection. Less immediate injection site pain was observed with Priorix than with M-M-R II . Vaccine diluent or formulation may influence level and duration of injection pain. Abstract: Purpose: The risk of post-vaccination adverse events (AEs) is a primary public health concern. Among the AEs, pain is a significant source of anxiety for both children and their parents. This review describes and assesses the intensity of pain experienced by children post-vaccination with widely used Measles–Mumps–Rubella (MMR) vaccines. Methods: A systematic literature search was conducted in Pubmed, Embase and Cochrane to identify publications describing immediate pain at injection site (primary objective) or pain within days (secondary objective) after 2 specific MMR vaccines. Immediate pain ('acute pain' according to the Brighton Collaboration case definition) was defined as pain occurring at the time or within 5 min of injection. Results: Four studies, which compared the intensity of immediate injection site pain experienced by children after MMR vaccination, were identified. Various pain assessment tools and methods were used to quantify the intensity of pain, including the median difference in Visual Analog Scale scores between vaccine groups. All four studies showed significantly less immediate pain caused by Priorix (GSK Vaccines) compared with M-M-R II (Merck & Co., Inc.). Conclusions: To our knowledge, this review summarizes for the first time the available scientific evidence on the intensity of pain following different MMR vaccines. It highlights that MMR vaccines can differ in terms of immediate pain. Further research may be needed to better understand the underlying reason for this observation. In this context, it is very important to understand which physicochemical properties are most relevant for the immediate pain profile of a vaccine to thereby support the development of vaccines with the best possible immediate pain profile.